INTERPRETER OR MEDIATOR? FROM COLONIZATION TO GLOBALIZATION - Lopes, Isabelle Tulekian (2019)
Along history, the interpreter’s role has always been central, allowingcommunication between people of different cultures and languages. Whereascolonization was a good example of the linguistic domination imposed by theEuropean nations over the colonized territories, the situation seems to be quitedifferent today. Globalization has brought migrant flows to the state members ofthe European Union, which at a certain time opened its doors to immigration. Inthis context, the European authorities stressed the necessity and political will toorganize and regulate migrant flows inside and outside the Schengen area. One ofthe instruments for the application of these measures is, no doubt, thedevelopment of a network of community interpreters who, as interculturalmediators, will make communication possible with migrant people and will workfor the integration of these people in the European society. Communityinterpreters work in public services, such as courts, police stations, hospitals, socialservices and schools. This study gives the bases for a reflection about skills andtraining that community interpreters need to develop, in the context describedabove, to reach the best standard of quality in their profession.